Rural youth out-migration and education: challenges to aspirations discourse in mobile modernity. Issue 3 (4th May 2017) - Corbett, Michael; Forsey, Martin
ABSTRACT: We argue here that critical educational scholarship is crucial to developing educational analysis attuned to the nuances of place, mobility, and change in rural locations. Critical sociological analysis, we argue, can also nuance and complicate simplistic portrayals of rural communities and their social, economic, and cultural character. Two central narratives in rural education today relate first, to the economic and social problems faced by challenged 'left behind' communities faced by depopulation and restructuring, and second, 'boomtown' communities that experience rapid infusions of wealth and population. We offer two linked case studies from Australia and Canada that draw on what we call a rural sociological imagination to interrogate how education is framed in contemporary convergences of history and biography in rural locations. These framings complicate and even confound meritocratic and human capital assumptions that underpin contemporary educational policy discourse, particularly as it relates to rural education.